1991
DOI: 10.1590/s0034-89101991000500005
|View full text |Cite
|
Sign up to set email alerts
|

Interações de planorbídeos vetores da esquistossomose mansoni e o problema da expansão de endemia na região Amazônica

Abstract: "No tocante a sua vegetação, a planta convém com a besta bruta e, por sentimento, o animal brutal com o homem, que se conforma ao resto dos astros por sua inteligência; essa ligação procede tão apropriadamente que parece uma corda estendida desde a primeira causa até as coisas baixas e ínfimas, por uma ligação recíproca e contínua; de sorte que a virtude superior, expandindo seus raios, chegará a tal ponto que, se lhe tocarmos uma extremidade tremerá e fará mover o resto" (C.G. Porta. Magie Naturelle, 1650).VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…The role of human migration in the geographic spread of the disease is well known, and also its association, in Brazil, with water management infrastructure-especially small dams-at the semi-arid part of the country. Streams in the Amazon were found to harbor at least eight species of snail hosts susceptible to S. mansoni infection (Valadão and Milward-de-R, 1991). The reporting of the first autochthonous human case of schistosomiasis (eastern Amazon) dates back to the late 1940s but the disease has remained restricted to discrete foci at the periphery of urban areas.…”
Section: Schistosomiasismentioning
confidence: 99%
“…The role of human migration in the geographic spread of the disease is well known, and also its association, in Brazil, with water management infrastructure-especially small dams-at the semi-arid part of the country. Streams in the Amazon were found to harbor at least eight species of snail hosts susceptible to S. mansoni infection (Valadão and Milward-de-R, 1991). The reporting of the first autochthonous human case of schistosomiasis (eastern Amazon) dates back to the late 1940s but the disease has remained restricted to discrete foci at the periphery of urban areas.…”
Section: Schistosomiasismentioning
confidence: 99%
“…Although B. amazonica and B. occidentalis have not yet been found to be naturally infected with S. mansoni (Coimbra Jr. et al 1984;Valadão and Milward-De-Andrade 1991), in vitro studies performed by Paraense and Correa (1982), and Coimbra Jr. and Engel (1982), using strains of the pathogen and snails from Rondônia, showed that B. amazonica is susceptible to infection by the trematode, at very low rates. However, B. occidentalis was not found to be a good host, either in the above-mentioned studies or in others performed by Fernandez and Thiengo (2006) using B. occidentalis from the state of Mato Grosso.…”
Section: Discussionmentioning
confidence: 99%
“…As condições climáticas locais parecem mais propícias à ocorrência de Biomphalaria tenagophila, tendo influenciado seu predomínio sobre Biomphalaria glabrata, que é o vetor principal da esquistossomose no Brasil 28 . Na área da UHER, Biomphalaria tenagophila foi encontrada em diversos pontos de coleta, no entanto foi mais numerosa em dois córregos que, em virtude de obras da usina, apresentaram a velocidade do fluxo reduzida na FC.…”
Section: Discussionunclassified